Hadis Kepemimpinan: Apakah Boleh Tidak Taat Pemimpin? - Delfi Yanti (Al-Thiqah: Journal of Hadith and Prophetic Tradition, 2025)
This article examines prophetic traditions (hadith) on leadership, focusing on the boundaries of obedience to rulers. Using a qualitative library research method, data were collected from canonical hadith compilations and supported by secondary literature in Islamic studies. The analysis employed thematic and descriptive approaches to explore the ethical principles underlying leadership in Islam. The findings indicate that while obedience to leaders is an essential principle to maintain social order, it is not absolute; obedience ceases when leaders command actions contrary to the teachings of Islam. This study highlights the ethical balance between loyalty and resistance, offering contemporary insights into Islamic political ethics and their relevance in addressing modern challenges of authoritarianism.